Strategi Pemenangan Caleg Partai Gerindra pada Pemilihan Umum Legislatif 2014 - Halimur Rosyid (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Legislative elections in 2014 by using an open-list proportional system has led to intense competition among the candidates in getting the sound. All the strategies, tactics and methods used by the candidates to be able to win the election. Therefore, the use of appropriate strategies become very important. This study aims to identify winning strategies Gerindra party candidates in legislative elections in 2014 in East Java. This study was conducted in East Java, involving several candidates Gerindra the qualitative descriptive method and interactive analysis. The fresults of in this study reveal that the use of marketing strategies politics candidates with 4P method, namely positioning, policy, party, and presentation. In the fourth method implementing the strategy, first define the target candidate region winning in the constituency (electoral district), respectively, this strategy is called a centralized marketing strategy. In addition, the challenges and barriers faced by candidates in the 2014 legislative elections more on the severity of internal competition among candidates in the party, such as money politics, black campaign, apathy politics, and the plots overlap among candidates in base the same choice.